Length–weight relationships of 11 deep‐sea fishes from the western Bay of Bengal and Andaman waters, India. (20th April 2018) - Aneesh Kumar, K. V.; Thomy, R.; Manjebrayakath, H.; Sudhakar, M.
Summary: Length–weight relationships (LWRs) are presented for 11 deep‐sea fishes caught in the western Bay of Bengal and Andaman waters during August 2010 using a 38 m high speed demersal trawl II (HSDT II, crustacean version, codend mesh size 40 mm) and a 45.6 m Expo model demersal trawl (codend mesh size 30 mm). The b values ranged from 2.34 to 3.3 and the coefficient of variation ( r 2 ) ranged from .82 to .98. LWR estimates of eight deep‐sea fishes are provided for the first time. The estimated LWR values were compared with the Bayesian LWR estimates available in FishBase, based on models developed to improve the accuracy and predictability of species‐specific growth parameters of data‐poor species.